Representing the location of manipulable objects in shape-selective occipitotemporal cortex: Beyond retinotopic reference frames?. (September 2018) - Zopf, Regine; Butko, Marina; Woolgar, Alexandra; Williams, Mark A.; Rich, Anina N.
Abstract: When interacting with objects, we have to represent their location relative to our bodies. To facilitate bodily reactions, location may be encoded in the brain not just with respect to the retina ( retinotopic reference frame), but also in relation to the head, trunk or arm (collectively spatiotopic reference frames). While spatiotopic reference frames for location encoding can be found in brain areas for action planning, such as parietal areas, there is debate about the existence of spatiotopic reference frames in higher-level occipitotemporal visual areas. In an extensive multi-voxel pattern analysis (MVPA) fMRI study using faces, headless bodies and scenes stimuli, Golomb and Kanwisher (2012) did not find evidence for spatiotopic reference frames in shape-selective occipitotemporal cortex. This finding is important for theories of how stimulus location is encoded in the brain. It is possible, however, that their failure to find spatiotopic reference frames is related to their stimuli: we typically do not manipulate faces, headless bodies or scenes. It is plausible that we only represent body-centred location when viewing objects that are typically manipulated. Here, we tested for object location encoding in shape-selective occipitotemporal cortex using manipulable object stimuli (balls and cups) in a MVPA fMRI study. We employed Bayesian analyses to determine sample size and evaluate the sensitivity of our data to test the hypothesis that location can be encoded in a spatiotopic reference frame in shape-selective occipitotemporal cortex over the null hypothesis of no spatiotopic location encoding. We found strong evidence for retinotopic location encoding consistent with previous findings that retinotopic reference frames are common neural representations of object location. In contrast, when testing for spatiotopic encoding, we found evidence that object location information for small manipulable objects is not decodable in relation to the body in shape-selective occipitotemporal cortex. Post-hoc exploratory analyses suggested that spatiotopic aspects might modulate retinotopic location encoding. Overall, our findings provide evidence that there is no spatiotopic encoding that is independent of retinotopic location in shape-selective occipitotemporal cortex.